The rise and fall of differentiated sex chromosomes in geckos - Rovatsos, Michail; Farkačová, Klára; Altmanová, Marie; Johnson Pokorná, Martina; Kratochvíl, Lukáš (Molecular ecology, 2019)
Amniotes possess variability in sex determination, ranging from environmental sex determination to genotypic sex determination with differentiated sex chromosomes. Differentiated sex chromosomes have emerged independently several times. Their noteworthy convergent characteristic is the evolutionary stability, documented among amniotes in mammals, birds, and some lineages of lizards, snakes and turtles. Combining the analysis of multiple partial transcriptomes with the comparison of copy gene numbers between male and female genomes, we uncovered partial gene content of the highly differentiated ZZ/ZW sex chromosomes in the gecko genus Paroedura. The differentiated ZZ/ZW sex chromosomes of these geckos share genes with the part of the chicken chromosome 4 homologous with the XX/XY sex chromosomes of viviparous mammals and the ZZ/ZW sex chromosomes of lacertid lizards, as well as with the chicken chromosome 15, homologous with the XX/XY sex chromosomes of iguanas and ZZ/ZW sex chromosomes of softshell turtles. Along with other analogous cases, this finding reinforces the observation that particular chromosomes are repeatedly coopted for the function of sex chromosomes in amniotes. Notably, according to the phylogenetic distribution, the subclade of the genus Paroedura represents a rare case of the reversal of the for a considerable evolutionary time highly differentiated ZZ/ZW sex chromosomes back to poorly differentiated state.
Keywords: reversal; kur domácí; transkriptom; Sex Chromosomes; Male; Chromosome Mapping; pohlavní chromozomy; Mammals; homology; fylogeneze; Chickens; Sex Determination Processes; Phylogeny; cooption; Transcriptome; biologická evoluce; mužské pohlaví; Turtles; Lizards; ještěři; savci; reptiles; Animals; sex chromosomes; ženské pohlaví; Biological Evolution; mapování chromozomů; amniota; zvířata; procesy určující pohlaví; želvy; Female